NONLINEAR FRACTALS AND EXCITON FORMATIONS IN NANOSTRUCTURED SEMICONDUCTORS - Zhanabayev, Z. Zh.; Grevtceva, T. Yu.; Almasbekov, N. E. (Recent Contributions to Physics, 2017)
We suggest the fractal model for the description energy spectra of excitons in amorphous and porous semiconductors. Because of theirs chaotic structure the famous analogy of exciton to hydrogen-like atom is insufficient. We obtain equations for energy of exciton, biexciton and trion depending on photon energy. Comparison of results of our theory to experimental data of the last years is given in the paper. Theory shows the existence of most universal regularities of dynamical systems.